The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.3389/fpsyt.2023.1156235
|View full text |Cite
|
Sign up to set email alerts
|

Current insights of community mental healthcare for people with severe mental illness: A scoping review

Abstract: BackgroundFor the last four decades, there has been a shift in mental healthcare toward more rehabilitation and following a more humanistic and comprehensive vision on recovery for persons with severe mental illness (SMI). Consequently, many community-based mental healthcare programs and services have been developed internationally. Currently, community mental healthcare is still under development, with a focus on further inclusion of persons with enduring mental health problems. In this review, we aim to prov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 102 publications
0
3
0
Order By: Relevance
“…Our ndings reveal that longstanding therapeutic relationships with a known and trusted therapist positively affected health, well-being, and recovery. Other studies have similarly found that a mutual relationship of trust is imperative for su cient mental healthcare (20,25,51).…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Our ndings reveal that longstanding therapeutic relationships with a known and trusted therapist positively affected health, well-being, and recovery. Other studies have similarly found that a mutual relationship of trust is imperative for su cient mental healthcare (20,25,51).…”
Section: Discussionmentioning
confidence: 92%
“…Previous research has highlighted an inverse association between social network size, psychopathology, and illness symptoms in SMI (3). Social network size does not consistently correlate with reported loneliness, indicating that the quality of relationships may be more important than quantity (20). In addition, the frequency of interactions with friends positively predicts clinical recovery in psychosis over two years (69).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Over the past 20 years, capacities for individuals with mental disabilities have steadily increased, particularly in the area of outpatient assisted living. However, this increase in housing assistance has not been matched by a corresponding rise in housing options for the most severely ill individuals [40][41][42]. This trend is concerning, especially given the widespread shortage of medical rehabilitation services for people with serious mental illnesses, particularly outpatient and mobile rehabilitation options.…”
Section: Expenses Related To Hospitalization In a Mental Health Facilitymentioning
confidence: 99%